2015
DOI: 10.1007/s11999-015-4283-0
|View full text |Cite
|
Sign up to set email alerts
|

Morbid Obesity: Increased Risk of Failure After Aseptic Revision TKA

Abstract: Background Patients with obesity are known to have a higher risk of complications after primary TKA; however, there is a paucity of data regarding the effects of obesity with revision TKAs. Questions/purposes We asked the following questions : (1) Are patients with morbid obesity (BMI C 40 kg/m 2 ) at greater risk for repeat revision, reoperation, or periprosthetic joint infection (PJI) compared with patients without obesity (BMI \ 30 kg/m 2 ) after an index revision TKA performed for aseptic reasons? (2) Do p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 29 publications
3
24
1
9
Order By: Relevance
“…17,[27][28][29] Obesity has been identified as a possible risk factor for reinfection in the primary and revision TKA settings. 30,31 In this study, we found an association with advanced age and diabetes as a risk factor for reinfection. Our study does have limitations given the inherent challenges of a large database study that relies on accurate coding.…”
Section: Discussionsupporting
confidence: 55%
“…17,[27][28][29] Obesity has been identified as a possible risk factor for reinfection in the primary and revision TKA settings. 30,31 In this study, we found an association with advanced age and diabetes as a risk factor for reinfection. Our study does have limitations given the inherent challenges of a large database study that relies on accurate coding.…”
Section: Discussionsupporting
confidence: 55%
“…Obesity has been an important issue not only in primary TKA but also in revision TKA. Watts et al 27 reported that morbidly obese patients (BMI ! 40 kg/m 2 ) had significantly higher rates of repeat revision, reoperation, and PJI after aseptic revision TKA when compared with patients without obesity (BMI < 30 kg/m 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…40 matched to 120 patients with BMI < 30 and found increased risk of repeat revision and prosthetic joint infection, as well as worse implant survival and Knee Society pain and function scores in the morbidly obese cohort. 36…”
Section: Effects Of Obesity On Tibial Implantmentioning
confidence: 99%